Savings, Financial Development, and Economic Growth in the Arab Republic of Egypt Revisited - Hussein, Khaled; Mohieldin, Mahmoud; Rostom, Ahmed (World Bank, Washington, DC, 2017)
Private savings play a pivotal role in financing development and sustaining growth. Recently, there have been many theoretical developments that underpin key determinants of savings behavior, many of which merit empirical investigation. Understanding the dynamics of the determinants of savings is crucial to inform economic policy and devise reform programs. This paper builds on earlier work examining the stability of the long-run relationship between the real interest rate, financial saving, and total saving during 1960 to 1990. The paper extends the scope of the empirical investigation of the determinants of private savings behavior in the Arab Republic of Egypt, and considers the effect of financial development. The analysis uses quarterly data covering 1991–2010, adopting a vector error correction model. The key findings attest that private savings in Egypt follow the Life Cycle Model in the long term. Controlling for population growth, the analysis finds that the real interest rate and financial development are key determinates for real private savings in the long run. The negative long-run relation between the real interest rate and private savings holds under the proposed model structure as well as for that in the earlier work. However, in the short run, inflation and exchange rate movements are key determinants for private savings decisions. Robust economic policies, inclusive of macroeconomic and monetary measures, are prerequisites for maximizing private savings and financing growth in Egypt.